Canakinumab in adults with steroid‐refractory pyoderma gangrenosum. (16th October 2015) - Kolios, A.G.A.; Maul, J.‐T.; Meier, B.; Kerl, K.; Traidl‐Hoffmann, C.; Hertl, M.; Zillikens, D.; Röcken, M.; Ring, J.; Facchiano, A.; Mondino, C.; Yawalkar, N.; et al.
Summary: Background: Pyoderma gangrenosum (PG) is a rare, neutrophilic, ulcerative skin disease that is difficult to treat, especially when unresponsive to steroids. Objectives: To determine whether canakinumab is an effective and safe treatment in PG. Methods: Five adult patients with clinically and histologically confirmed steroid‐refractory PG were enrolled in this prospective open‐label study. They received canakinumab 150 mg subcutaneously at week 0 with an optional 150 mg at week 2 in case of an inadequate response [Physician's Global Assessment (PGA) ≥ 2], and an optional 150–300 mg at week 8 depending on PGA. The primary clinical end point was clinical improvement (PGA at least −1 from baseline) and/or complete remission (PGA 0 or 1) at week 16. Real‐time quantitative polymerase chain reaction was performed on skin samples to quantify cytokine mRNA levels. Results: Interleukin (IL)‐1β and its known target genes IL6, CXCL8 and IL36A were significantly increased in lesional skin of PG. Under canakinumab therapy, four of five patients showed a decrease in target‐lesion size, PGA and Dermatology Life Quality Index (DLQI), and three of five achieved complete remission. The mean diameter of target lesions decreased from 4·32 ± 2·6 cm at visit 1 to 0·78 ± 1·3 cm at visit 7 ( P = 0·03). Mean DLQI decreased from 15 ± 5 at visit 1 to 8 ± 4 by visit 7 ( P = 0·01). Adverse effects were reported in two patients: fatigue in one and worsening of disease at a nontarget lesion in the other. Conclusions: Our data indicate that IL‐1β plays a key pathogenic role in PG and canakinumab may represent a therapeutic option for steroid‐refractory PG. Abstract : What's already known about this topic? Pyoderma gangrenosum is a rare, difficult‐to‐treat neutrophilic ulcerative skin disease frequently associated with systemic disease, and treatment can be challenging. The successful use of canakinumab in pyoderma gangrenosum has been reported in the context of PAPA syndrome (pyogenic arthritis, pyoderma gangrenosum and acne), a recently characterized rare autosomal dominant autoinflammatory disease of early onset. What does this study add? The proinflammatory cytokine interleukin (IL)‐1β is abundant in its active form in human pyoderma gangrenosum skin lesions. Blockade of IL‐1β with the monoclonal antibody canakinumab can improve steroid‐resistant pyoderma gangrenosum. This provides novel evidence that IL‐1β plays a role in the pathogenesis of pyoderma gangrenosum. Linked Comment: Costanzo, Br J Dermatol 2015;173 : 1124 .